2022
DOI: 10.1001/jamanetworkopen.2022.27738
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diet and Physical Activity With All-Cause Mortality Among Adults With Parkinson Disease

Abstract: IMPORTANCEGreater diet quality and physical activity level are associated with a lower risk of developing Parkinson disease (PD). However, information regarding the association between lifestyle behaviors and survival after PD diagnosis remains limited. OBJECTIVE To examine the association of prediagnosis and postdiagnosis overall diet quality and physical activity with all-cause mortality among individuals with PD. DESIGN, SETTING, AND PARTICIPANTS This population-based cohort study analyzed male participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…However, the current study also suggests that a healthy diet and higher levels of recreational physical activity may accomplish what medical intervention thus far has not been able to do: slow the pace of progression; that is, if the factors associated with PD susceptibility and mortality were the same factors associated with disease severity over time. To this end, other studies have shown healthy food and/or physical activity to be inversely associated with, and thus possibly lead to, improved nonmotor features of PD, such as constipation, excessive daytime sleepiness, and depression, that greatly affect patients’ health-related quality of life .…”
mentioning
confidence: 74%
See 4 more Smart Citations
“…However, the current study also suggests that a healthy diet and higher levels of recreational physical activity may accomplish what medical intervention thus far has not been able to do: slow the pace of progression; that is, if the factors associated with PD susceptibility and mortality were the same factors associated with disease severity over time. To this end, other studies have shown healthy food and/or physical activity to be inversely associated with, and thus possibly lead to, improved nonmotor features of PD, such as constipation, excessive daytime sleepiness, and depression, that greatly affect patients’ health-related quality of life .…”
mentioning
confidence: 74%
“…Because PD has a long prodromal period, it is of utmost importance to find factors that may change the pathological cascade of events even before PD diagnosis and help slow neurodegenerative progression. The results of the cohort study by Zhang et al are promising and suggest that maintaining a healthy diet and higher levels of recreational physical activity is associated with improved patient outcome by preventing earlier mortality. These results not only reinforce the public health recommendations to engage in these behaviors for staying healthy in general but also add to a growing body of evidence of such behaviors providing protection against PD-related neurodegeneration specifically .…”
mentioning
confidence: 99%
See 3 more Smart Citations